Point Cloud Semantic Segmentation Based on Rotation Invari-ance and Feature Aggregation - Liang, Xiujuan; Zhang, Shiye (International Journal of Computer Science and Information Technology, 2026)
As a key task in 3D scene understanding, point cloud semantic segmentation has broad application prospects in fields such as autonomous driving and robot navigation. Existing point cloud segmentation methods suffer from insufficient local feature extraction and a lack of effective integration of global contextual information, leading to inaccurate recogni-tion and incomplete segmentation of categories with similar surface textures and geometric structures. In view of this, this paper proposes an improved point cloud segmentation method for RandLA-Net : (1) Local polar coordinate posi-tion encoding module is introduced to eliminate the impact of Z-axis rotation on feature learning; (2) Global information acquisition module composed of attention mechanisms is constructed to enhance the network's contextual perception ability; (3) Hybrid pooling mechanism is integrated to improve the extraction of local features. The proposed method is evaluated on the self-built HPU dataset and public datasets S3DIS and Toronto-3D. The results show that the improved network achieves mean intersection over union (mIoU) values of 90.7%, 71.2%, and 76.4% respectively, demonstrating improvements compared to other algorithms. The model exhibits excellent generalization and segmentation perfor-mance in different types of point cloud scenes.